Attitude of Farmers Towards Use of Combine Harvester - Lambe, S. P. , P. K. Wakle; A. S. Gomase (Indian Journal of Extension Education, 2014)
The present study was undertaken in Akola district of Maharashtra State. An exploratory design of social research was used. A sample of 100 farmers who harvested their crop with the help of combine harvester were drawn and information was collected which was considered for tabulation and analysis of the data. The farmers who used combine harvester were in middle age group (45.00%), educated up to high school level (48.00 %) and possessed large land holding (50.00%). Half of the respondents possessed the hand operated and bullock drawn implements. Very few of them possessed the power operated implements. In case of attitude, the farmers showed the favorable attitude (65.00%) towards the use of combine harvester.